Maternal Anxiety Before Amniocentesis and Clinical Outcomes for Prenatal Diagnosis of Down Syndrome in Loeng Nok Tha Crown Prince Hospital, Yasothon Province, Thailand - Hunchana, Pawina (Srinagarind Medical Journal, 2024)
Objective: The purpose of the current study was to assess the maternal anxiety before amniocentesis and clinical outcomes for prenatal diagnosis of Down syndrome in Loeng Nok Tha Crown Prince Hospital, Yasothon province in Thailand. Materials and methods: This was a cross-sectional study, during the period of January 2019 to December 2023. Sample group were 93 pregnant women, divided into 52 cases of positive Q-Test screening (PQT) and 41 cases of the age over 35 years or more (advanced maternal age: AMA). Results: 60.22 % of pregnant women were high levels of anxiety about amniocentesis, 68.82% (64 people) accepted for amniocentesis, and mostly were performed at 16-18 weeks (70.97 %). The chromosome test results were abnormal in 6 people (9.38%). Conclusions: The goal for doctors is to ensure an enable pregnant women and their families to be able to make their own decisions with confidence, as this would help to reduce the fear and anxiety level, and consequently it will help them to accept and acknowledge the procedurals outcomes and reduce anxiety among pregnant women waiting to undergo an amniocentesis.